Isopropyl 2,5-anhydro-3,4-di-O-tert-butyldiphenyl-silyl-L-ribonate - Glawar, A. F. G.; Watkin, D. J.; Sanjayan, G. J.; Tranter, G. E.; Edwards, Alison A.; Fleet, George W. J. (Acta Crystallographica Section E - Structure Reports Online, 2005)
Determination of the crystal structure of the title compound, C40H50O5Si2, firmly established its relative configuration and hence that of some related tetrahydrofuran carboxylates. The material crystallizes with Z' = 2. Except for the chiral centres, the two independent molecules are related by a pseudo-centre of symmetry.

Novel series of oligomers from 4-aminomethyl-tetrahydrofuran-2-carboxylates with 2,4-cis and 2,4-trans stereochemistry - Edwards, Alison A.; Sanjayan, Gangadharar J.; Hachisu, Shuji; Tranter, George E.; Fleet, George W. J. (Tetrahedron, 2006)
Two tetrahydrofuran-based y-amino acids [2,4-cis and 2,4-trans] were subjected to iterative peptide-coupling procedures to afford dimeric, tetrameric and hexameric carbopeptoids in good yield. These homooligomers were prepared for secondary structural study-to ascertain the conformational preference inherent in the monomer units. The L-xylo oligomers were protected with triethylsilyl ethers to increase the range of solvents suitable for structural investigation. Initial secondary structure data indicate the presence of hydrogen-bonded conformations in the L-ribo series. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Foldamers; gamma amino acids; Peptidomimetics; sugar amino acids

Synthesis of 4-aminomethyl-tetrahydrofuran-2-carboxylates with 2,4-cis and 2,4-trans relationships - Edwards, Alison A.; Sanjayan, Gangadhar J.; Hachisu, Shuji; Soengas, Raquel; Stewart, Alistair; Tranter, George E.; Fleet, George W. J. (Tetrahedron, 2006)
Templated tetrahydrofuran-based gamma-azido esters were prepared with the C-2 and C-4 functionalities in cis and trans relative configurations. This was achieved by ring contraction of the suitably protected 2-O-triflates of pentono-1,5-lactones (D-ribose and L-arabinose) with subsequent introduction of the azide via the 4-O-triflate. Access to a corresponding beta-azido ester was achieved in good yield. Little elimination product was observed by introduction of the azide via the 3-O-triflate. These azido esters are scaffolds. which may be predisposed to adopt secondary structural motifs, for example. for use as peptidomimetics; they may also be utilised for the preparation of stereodiverse compound libraries. (c) 2006 Elsevier Ltd All rights reserved.
Keywords: gamma amino acids; Peptidomimetics; scaffolds; sugar amino acids